Effect of an electron beam on a dual-frequency capacitive rf plasma: experiment and simulation. (1st September 2022) - Bogdanova, M; Lopaev, D; Zotovich, A; Proshina, O; Rakhimova, T; Zyryanov, S; Rakhimov, A
Abstract: One of the crucial challenges facing modern microelectronics is to provide plasma surface treatment at the single atomic level. To minimize defects in the underlying layers, these processes require ions with very low energies—lower than in conventional radio-frequency (rf) plasma and close to the binding energy of atoms. A conventional rf dual-frequency capacitively coupled plasma (df CCP) discharge with additional ionization by an electron beam is considered as a possible solution to this problem. This paper contains a study on the electron beam effect on 81 & 12 MHz plasma parameters such as electron energy probability function, plasma density, electron temperature and ion energy distribution at an rf-biased electrode. The experimental part of the study includes measurements carried out in an asymmetric rf df CCP discharge in Ar at 100 mTorr pressure using a Langmuir probe, a hairpin-probe, and a retarding field energy analyzer. The behavior of plasma parameters is considered in the different types of plasma: electron beam plasma, when no rf power is applied, as well as rf plasma with and without an electron beam. The 1D PIC MCC simulation is used to analyze the effect of an electron beam on the df rf plasma. The obtained results showed that the electron temperature and, accordingly, the energy of ions coming at the electrode surface can be lowered. The use of an electron beam in a df CCP discharge allows to control the plasma density, electron temperature and ion energy spectrum in the low-energy range, which can be of essential interest for atomic layer etching and atomic layer deposition technologies.